Indigenous fungi inoculation drives organic carbon accumulation and phosphorus transformation in coal gangue-based artificial soil: role of mineral-bioactivation - Zhang, Huofeng; Xu, Runan; Quan, Yijie; Xue, Donghe; Hu, Ling; Yang, Yan; Dong, Ying; Wang, Wei; Bo, Huijuan; Zhang, Qiang; Xu, Minggang; Jin, Dongsheng (Frontiers in Microbiology, 2026)
Coal gangue accumulation occupies extensive land areas, causing severe environmental pollution and degrading soil quality in mine reclamation sites. In this study, we aimed to identify the optimal inoculum concentration that maximizes physicochemical improvement and biological stability. The bioactivation effects of indigenous fungal inocula (1–5%) on coal gangue (C) and coal gangue-loess mixtures (M) were assessed by analyzing fungi abundance, pH, electrical conductivity (EC), total organic carbon, available phosphorus, and mineral composition. The indigenous fungi J-Z, isolated from coal gangue dumps, exhibited optimal bioactivation performance at moderate inoculum concentrations (3–4%). The pH initially decreased during days 7–14 and subsequently stabilized, with the 3% inoculum (M3) and 4% (M4) inoculum treatments exhibiting the strongest buffering capacity. EC increased with inoculum concentration until reaching equilibrium. Higher inoculum concentrations enhanced total organic carbon accumulation in both the C and M systems, especially under M3 and M4 treatments. Available phosphorus increased with inoculum concentration, peaking in M4 (3.0–3.5 mg·kg−1) after 60 days. XRD analysis revealed a significant transformation from Strengite to Monetite in the M4 treatment. Organic acid analysis indicated that citric acid was the primary driving force behind this transformation. Overall, M4 achieved the optimal balance between fungi activation and physicochemical stability. This study establishes a scientific framework for the sustainable utilization of coal gangue as a reclamation substrate through coupled biochemical processes involving fungi activation, mineral transformation, and nutrient stabilization.